Assistance for IKM Aredo Tidar Sawe, Magelang City, in enhancing the slondok business - Retno Rusdjijati; Mayang Aprelia; Abidah Ardelia Belva Fithriyah; Putri Rayhandita; Aprilia Devi Indriani; Fika Agus Tina (Universitas Muhammadiyah Magelang, 2025)
IKM Aredo is a home-based food processing industry located in Kampung Tidar Sawe, Tidar Selatan Subdistrict, Magelang Selatan District, Magelang City. This business has been operating for ten years but has not yet developed optimally. This community service activity aims to assist IKM Aredo in enhancing knowledge and skills related to good production processes, creating attractive and protective packaging, and maintaining regular business bookkeeping. The activities were conducted in the form of socialization, training, practice, technology implementation, mentoring, monitoring, and evaluation. The results of this assistance include increased knowledge of good production practices, improved product packaging with safe and attractive labeling, and the implementation of regular business bookkeeping by the partners.